Cucurbitacin E Inhibits Proliferation and Migration of Intestinal Epithelial Cells via Activating Cofilin - Song, Huapei; Wang, Yu; Li, Li; Sui, Hehuan; Wang, Pei; Wang, Fengjun (Frontiers in Physiology, 2018)
The proliferation and migration of intestinal epithelial cell is important to the barrier integrity of intestinal epithelium. Cucurbitacin E (CuE) is one of the tetracyclic triterpenoids extracted from the cucurbitaceae that has been shown to inhibit cancer cell growth, tumor angiogenesis and inflammatory response. Nevertheless, the role of Cucurbitacin E in regulating the proliferation and migration of intestinal epithelial cells remain unclear.. In this study, the human intestinal epithelial cell line Caco-2 was treated with CuE and the effects of CuE on cell cycle, proliferation, migration and actin dynamics in Caco-2 cells were investigated successively. We found that CuE significantly inhibited the cell proliferation and migration, inducing the cell cycle arrest in G2/M phase and disrupting the actin dynamic balance in Caco-2 cells. Finally, we showed that CuE inhibited cofilin phosphorylation by suppressing the phosphorylation of both LIM kinase (LIMK)1 and LIMK2 in vitro, resulting in the activation of cofilin, which is closely associated with cell proliferation and migration. Therefore, our studies provided the first evidence that CuE inhibited the proliferation and migration of intestinal epithelial cells via activating cofilin, and CuE is a potential candidate in intestinal disease therapy.